Glimpses Into My Compositional Style and Techniques : Text and Musical Examples - Badian, Maya (Lucian Badian Editions, 2014)

Shock, glam, punk - Desfossés, Félix B. (No Speed Limit (1964-1989). L’évolution du métal québécois, 2014)

Soprano Pierrette Alarie (1921-2011), tenor Léopold Simoneau (1916-2006). Part 1 - Duffie, Bruce (Opera Journal, 2014)
Keywords: Interviews; Music; Musical performances; Musicians & conductors; Singers

Soprano Pierrette Alarie (1921-2011), tenor Léopold Simoneau (1916-2006). Part 2 - Duffie, Bruce (Opera Journal, 2014)
Keywords: Accompanists; Composers; Librettists; Music; Musical performances; Musicians & conductors; Opera; Singers

Les Daraîche, la famille royale du country - Dumas, Carmel (Magazine Gaspésie, 2014)
Un article de la revue Magazine Gaspésie, diffusée par la plateforme Érudit.

Michel Louvain. Sans âge - Gignac, Benoît (Éditions Caractère, 2014)
Découvert au milieu des années 50, admiré et adulé, Michel Louvain fait encore battre les coeurs près de 60 ans après avoir amorcé sa carrière. Ce livre-coffret retrace le parcours irréprochable de cet artiste accompli, qui a remporté les honneurs autant pour ses performances sur disque, sur scène et à la télévision que pour son soutien à des causes sociales.

Claude Vivier: A Composer’s Life - Gilmore, Bob (University of Rochester Press, 2014)
Claude Vivier's haunting and expressive music has captivated audiences around the world. But the French-Canadian composer is remembered also because of the dramatic circumstances of his death: he was found murdered in his Paris apartment at the age of thirty-four. Given unrestricted access to Vivier's archives and interviews with Vivier's family, teachers, friends, and colleagues, musicologist and biographer Bob Gilmore tells here the full story of Vivier's fascinating life, from his abandonment as a child in a Montreal orphanage to his posthumous acclaim as one of the leading composers of his generation. Expelled from a religious school at seventeen for "lack of maturity," Vivier gave up his ambition to join the priesthood to study composition. Between 1978 and 1981 Vivier wrote the works on which his reputation rests, including 'Lonely Child', 'Bouchara', and the operas 'Kopernikus' and 'Marco Polo'. He went to Paris in 1982 to work on a new opera, the composition of which was interrupted by his murder. On his desk was the manuscript of his last work, uncannily entitled "Do You Believe in the Immortality of the Soul?" Vivier's is a tragic but life-affirming story, intimately connected to his passionate music. Bob Gilmore is a musicologist and performer and teaches at Brunel University in London. He is the author of 'Harry Partch: A Biography'.

Le Lunatique, « Le temps du changement » : Intimidation, ostracisme et homophobie dans le milieu hip-hop au Québec - Lamort, Kapois (Les boss du Québec. R.A.P. du fleur de lysée. Analyse socio-historique et sociologique du hip-hop dans la société québécoise, 2014)
Le tout premier livre monographique et scientifique axé sur la culture Hip-Hop au Québec, rédigé par Kapois Lamort, historien spécialiste diplômé de l’Université du Québec à Montréal ( UQAM); cet ouvrage retrace les 35 ans d’existence du H.I.P.H.O.P. à travers la société québécoise de 1979 à 2015

Mad Je Deviendrai : Les divas dans le hip-hop au Québec - Lamort, Kapois (Les boss du Québec. R.A.P. du fleur de lysée. Analyse socio-historique et sociologique du hip-hop dans la société québécoise, 2014)
Keywords: Italique avant les deux-points

In Search of a Different History: The Remains of Burlesque in Montreal - Mansbridge, Joanna (Canadian Theatre Review, 2014)
: Taking Elin Diamond’s and Rebecca Schneider’s recent work in drama and performance studies as a starting point, this essay looks at two eras of burlesque in Montreal—the 1940s-50s and 2012—tracing a shifting landscape of popular entertainment, politics, religion, and social attitudes toward female sexuality. There is a central question underlying this examination: Why burlesque? Why now (or, rather, again?). I argue that burlesque offers an archive that evokes a different, more glamorous history than the one passed down to women by second-wave feminism. Burlesque also provides an alternative to popular culture’s commodification of female sexuality, technology’s mediation of social life, and heteronormative culture’s privatization of sexuality, giving women—and men—a stage on which to make fun of our cultural fixation with sex and the female body. Both nostalgically looking back and eagerly reaching for the new, neo-burlesque repeats the past as it simultaneously reinvents it.
Publisher: University of Toronto Press

Nicole Lizée. Faisceaux imaginaires et cool media - McKinley, Maxime (La création musicale au Québec, 2014)

Native Classical: Musical Modernities, Indigenous Research Methodologies and a Kanienkéha (Mohawk) Concept of Non:wa (Now) - Witzleben, John Lawrence (Université du Maryland, 2014)
In this dissertation I explore how Indigenous methodologies that foreground cultural advocacy, revitalization, and education can be articulated using Indigenous language and cultural metaphor in research on North American Indian composers. Toward this end, I apply the Kanienkéha (Mohawk) concept of "non:wa" or "now" that also refers to three modes of perception–the now of the past, the present, and the future–toward understanding the intersection of innovation and tradition in classical Native music. This research joins the existing discourse that critiques binary oppositions separating Indigenous tradition (as past) and innovation (as present and future). Through interviews, fieldwork, and musical analysis, I illustrate Native values of interconnectedness, relationality, continuity, politics, and soundscapes in the processes of Native composition as well as the resultant works, I explore how these, in turn, may be understood through the application of Indigenous research techniques. In collaboration with a cohort of contemporary musicians, I look primarily at two Navajo composers–Raven Chacon and Juantio Becenti–and examine my own work as a composer, performer, and ethnomusicologist of Kanienkéha descent to explore the following questions: How can the topic of classical Native music best be served by using Indigenous methodologies in fieldwork, research, and representation and What is classical Native Music and is it different from other contemporary classical music styles? Drawing on the teachings of Indigenous dotahs (elders/teachers), the scholarship of ethnomusicologists, and examining oral and written tradition while using language and cosmology as cultural metaphors, I present a variety of possibilities for looking at Indigenous music through Indigenous eyes. Rather than offering a set of conclusions, I offer a set of tools for discussion and reflection: 1) how we might understand a definition of classical Native music; 2) how we are part